Analisis Partisipasi Investor dalam Menyampaikan LKPM Online: Studi Kasus di Kabupaten Klungkung - Suryani , Ni Luh Putu; Widnyani , Ida Ayu Putu Sri; Dewi, Nyoman Diah Utari (Penerbit Goodwood, 2024)
Purpose: The purpose of this research is to improve the effectiveness of the targeted monitoring system so that it can increase the responsiveness and participation of investors in submitting LKPM online. And also to identify and analyze the factors that become obstacles that hinder such participation. So that the government can monitor investment developments, ensure smooth business and provide an outline in formulating future policies, in order to create a conducive investment climate in Klungkung Regency. Research methodology: This research uses a qualitative method. With data collection techniques through interviews, observations and documentation. The sampling technique uses purposive sampling, on 35 business actors in the Klungkung Regency area. With a qualitative analysis method, using data triangulation analysis techniques, namely combining data from interviews, observations and documentation. Result: The results of this study show a correlation between the low level of online LKPM submission and the level of investor participation in Klungkung Regency, which is still relatively low. And also obtained a picture of the causal factors originating from internal factors and external factors of investors. And obtained several alternative solutions to overcome it, including competency development, information system development, improving infrastructure quality, implementing socialization, providing technical assistance, and periodic supervision. Limitation: The limitations of this research are, with a small number of participants, namely 35 investors, it certainly cannot represent a wider population or cannot be generalized to all investors. This research was also conducted in a short time, so it could not explore the topic in depth. Contribution: This research can produce valuable data and information about the level of participation and the factors that influence it. So that it can be used as a basis for further research to evaluate the effectiveness of policies in increasing the participation of investors.